Climatic determinants of diet and foraging behaviour in baboons - Hill, R; Dunbar, R (Kluwer Academic Publishers, 2002)
Baboons (Papio spp.) are characterised by a large degree of variation in foraging behaviour and dietary composition. Previous analyses have suggested that much of this can be traced to differences in ecological conditions between sites. The proximate mechanism underlying these relationships is assumed to be mediated via the impact of climatic conditions on food availability, and ultimately the impact that this has on dietary composition. This paper examines these relationships more explicitly. Data from 15 baboon populations were used to assess the relationship between foraging variables and dietary composition. Only feeding time showed significant relationships with dietary composition, with percentage of time spent feeding decreasing with proportion of fruit in the diet, and increasing with the proportion of subterranean items. No relationships were found between diet composition and moving time or day journey length, although significant relationships were found between these variables and group size. The proportions of feeding time spent feeding on fruit, subterranean items and leaves were functions of the ecological conditions experienced by that population, although no relationships were found for the percentage of feeding time devoted to flowers or animal material. The relationships between the proportion feeding time spent on fruits, leaves and subterranean items and ecological variables could be best explained through understanding the way in which bush and tree level vegetation respond to the climatic environment and the impact this has on fruit availability. In this respect, temperature and seasonality are the key climatic parameters. This provides good support for the idea that the proximate mechanism underlying the relationship between foraging time and ecological variables is mediated via the impact of the climatic environment on vegetation structure and food availability. Similar factors have been proposed to explain much of the geographic variation in species diversity, suggesting that these relationships have far wider relevance and may account for much of the observed geographical variation in mammalian behaviour.